Uncertainty quantification of thermal barrier coatings lifetime on rotating turbine blades considering chemo-thermo-mechanically coupling failure - Weiliang Yan; Cong Li; Qianqian Zhou; Yuqi Xie; Yu Sun; Li Yang; Yichun Zhou (Materials & Design)
The lifetime prediction of thermal barrier coatings (TBCs) on rotating turbine blades remains a significant challenge due to the complex service environment and multi-physics failure mechanisms. A computationally efficient multiscale uncertainty quantification model based on an adaptive Gaussian Process was developed. The model accounts for the coupled effects of thermal mismatch, interface oxidation, and creep at the microscale, while considering the interaction of gas thermal shock and high-speed rotation at the macroscale. The model was applied to quantify the uncertainty in damage evolution and service lifetime of TBCs on rotating turbine blades. Meantime, the key factors influencing TBCs failure are also analyzed. The prediction results revealed that after 600 cycles, the failure probability of TBCs on the suction side tip and the pressure side middle region of the rotating blade reached 80 %. This indicates that the spallation of TBCs has occurred in these regions, with an area of about 9 %. The spallation position and area of the experimental results are relatively consistent with the predicted results. The thermal expansion coefficient of the thermally grown oxide and temperature were identified as the most critical factors influencing TBCs lifetime.